Prehospital treatment of acute myocardial infarction - Raúl M. Valdesuso Aguilar; Caridad Hidalgo Barrios; Rafael León Díaz Rafael León Díaz; Alejandro Pérez (ECIMED, 2014)
We believe there is a group of measures that can be put into practice without great material efforts in order to reduce acute myocardial infarction mortality. As it is our objective to make people think of this topic, we provide some data taken from the medical literature. We also suggest some procedures that may benefit the patient.